2017
DOI: 10.1097/bpo.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Scoliosis Associated With Arthrogryposis Multiplex Congenita

Abstract: Scoliosis in children with arthrogryposis occurs in the minority of patients, but appears early, often present at birth. Curves can progress quickly. Treatment options include spine casting, bracing, expandable implant surgery, and spinal fusion. The goal is to allow as much chest growth and development as possible, along with a resulting well-balanced spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…In children with Amyoplasia or syndromic arthrogryposes, spinal deformities may be present at birth and truly are a contracture of the spine due to akinesia, reflecting the position of the fetus in utero (Drummond & Mackenzie, ; Komolkin, Ulrich, Agranovich, & van Bosse, ). Although these deformities are present at birth, they are not labeled “congenital scoliosis” as that term is used to describe abnormal spine alignment at birth associated with vertebral malformations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In children with Amyoplasia or syndromic arthrogryposes, spinal deformities may be present at birth and truly are a contracture of the spine due to akinesia, reflecting the position of the fetus in utero (Drummond & Mackenzie, ; Komolkin, Ulrich, Agranovich, & van Bosse, ). Although these deformities are present at birth, they are not labeled “congenital scoliosis” as that term is used to describe abnormal spine alignment at birth associated with vertebral malformations.…”
Section: Resultsmentioning
confidence: 99%
“…These “at‐birth” or essential spinal deformities may include “C”‐shaped thoracolumbar scoliosis with or without associated hyperlordosis (Greggi et al, ; Herron, Westin, & Dawson, ; Soultanis et al, ). Babies presenting with essential spine deformities generally have severe upper and lower limbs contractures, fibro‐fatty degeneration of the muscles and a more guarded potential for independent daily living and ambulation (Komolkin et al, ). Treatment may include early physiotherapy for stretching, bracing, and seat/bed modifications, with the goal of preventing rapid progression of the spine deformity, providing for stable seating, and positioning for comfortable sleep.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As scoliosis in AMC is unusual and the number of cases reviewed in previous studies is also relatively small, 16 there is no study that has directly compared the results of spinal deformity correction between AMC and AIS patients. This study showed that spinal deformity correction in patients with AMC differed in several ways from that in patients with AIS.…”
Section: Discussionmentioning
confidence: 99%